Circuit of Culture: A Critical Look at Dilbert and Workplace Learning - Vicki K. Carter; Sharon L. Howell (Adult Education Research Conference, 1998)
As a cultural artifact, the Dilbert comic strip has generated both amusement and consternation, particularly for corporate trainers. This paper summarizes a year of research on Dilbert and its surrounding discourse in order to extend the critique of corporate education and Human Resource Development (HRD) into the cultural realm.